Measurement of the Drell-Yan triple-differential cross section in pp collisions at root s=8 TeV - Çelebi, Emre; Çetin, Serkant Ali (SPRINGER, 2017)
This paper presents a measurement of the triple-differential cross section for the Drell-Yan process Z/gamma* -> l(+)l(-) where l is an electron or a muon. The measurement is performed for invariant masses of the lepton pairs, m(ll), between 46 and 200 GeV using a sample of 20.2 fb(-1) of pp collisions data at a centre-of-mass energy of root s = 8TeV collected by the ATLAS detector at the LHC in 2012. The data are presented in bins of invariant mass, absolute dilepton rapidity, vertical bar y(ll)vertical bar, and the angular variable cos theta* between the outgoing lepton and the incoming quark in the Collins-Soper frame. The measurements are performed in the range vertical bar y(ll)vertical bar < 2.4 in the muon channel, and extended to vertical bar y(ll)vertical bar < 3.6 in the electron channel. The cross sections are used to determine the Z boson forward-backward asymmetry as a function of vertical bar y(ll)vertical bar and m(ll). The measurements achieve high-precision, below the percent level in the pole region, excluding the uncertainty in the integrated luminosity, and are in agreement with predictions. These precision data are sensitive to the parton distribution functions and the effective weak mixing angle.
Keywords: Hadron-Hadron scattering (experiments)